Pengaruh Penggunaan Metode Bercerita Terhadap Kemampuan Kpgnitif Anak Usia 5-6 Tahun - Hasanah, Ina; Mulyono, Nono; Kuncoro, Agus (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2024)
This study aims to examine the effect of storytelling methods of the stories of the Prophets and Messengers on the cognitive abilities of children aged 5-6 years at RA Miftahul Hidayah, Cibeureum Village, Banjar City. The research method employed is an experimental design with a quasi-experimental two-group pretest-posttest design. Data were collected through pre-tests and post-tests conducted on two groups: the experimental group, which received the storytelling treatment, and the control group, which did not receive the treatment. The results showed that the average cognitive ability related to the stories of the Prophets and Messengers before the storytelling method was applied reached 83.89%, while after the application of the method, it increased to 98.89%. Data analysis revealed a significant difference in cognitive abilities between the experimental and control groups. These findings indicate that the use of the storytelling method of the Prophets and Messengers' stories has a positive effect on improving the cognitive abilities of children aged 5-6 years.